2020
DOI: 10.1186/s13102-020-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of typical handball characteristics on upper body posture and postural control in male handball players

Abstract: Background: Well defined constitutional parameters support the physical fatigue resistance in handball to maintain the performance level for the majority of actions. Ideal constitutional conditions are necessary to achieve these physiological advantages in handball. But limited knowledge exists about the upper body posture or the postural control in correlation to the Body Mass Index (BMI), playing years, playing position and throwing arm in professional male handball. Methods: Ninety-one male handball players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Since these police officers often wear a protective suit, it seems reasonable to assume that MSDs can develop from this and that these can be observed in the upper body posture. Video raster stereography is a technique that is already used to measure the upper body posture [32][33][34]. In addition, there are available current standard values depending on age, sex and BMI that can be used as reference values [32].…”
Section: Introductionmentioning
confidence: 99%
“…Since these police officers often wear a protective suit, it seems reasonable to assume that MSDs can develop from this and that these can be observed in the upper body posture. Video raster stereography is a technique that is already used to measure the upper body posture [32][33][34]. In addition, there are available current standard values depending on age, sex and BMI that can be used as reference values [32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that PC is deteriorated due to both local and general fatigue, increasing the risk for traumatic musculoskeletal injuries . Since athletic performances need simultaneously musculoskeletal system integrity and well-developed PC (Ohlendorf et al, 2020), investigating the effect of neuromuscular fatigue on PC in athletes has been an interest for many studies Troester and Duffield, 2019). In this context, PC was shown to be more disturbed by neuromuscular fatigue in females compared to males Whyte et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that PC is deteriorated due to both local and general fatigue, increasing the risk for traumatic musculoskeletal injuries (Gribble and Hertel, 2004 ; Pau et al, 2014 ). Since athletic performances need simultaneously musculoskeletal system integrity and well-developed PC (Ohlendorf et al, 2020 ), investigating the effect of neuromuscular fatigue on PC in athletes has been an interest for many studies (Thiele et al, 2015 ; Troester and Duffield, 2019 ). In this context, PC was shown to be more disturbed by neuromuscular fatigue in females compared to males (Gribble and Hertel, 2004 ; Whyte et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%